LEXICO-SEMANTIC ANALYSIS OF WEATHER ADJECTIVES (World Bulletin of Social Sciences, 2023)
Language serves as a powerful lens through which we interpret and communicate our experiences, including the ever-changing phenomenon of weather. This article conducts a thorough lexico-semantic analysis of weather adjectives, exploring their nuances, cultural implications, and cognitive dimensions. By investigating the semantic fields, usage patterns, and emotional connotations of these adjectives, we aim to uncover the intricate relationship between language and the perception of weather.